Topical antifungal keratitis therapeutic potential of Clitoria ternatea Linn. flower extract: phytochemical profiling, in silico modelling, and in vitro biological activity assessment - Yolin Angel, Poomany Arul Soundara Rajan; Jeyakumar, Palanisamy; Jasmin Suriya, Arul Raj; Sheena, Aliyas; Karuppiah, Ponmurugan; Periyasami, Govindasami; Stalin, Antony; Murugan, Kasi (Frontiers in Microbiology, 2024)
Fungal keratitis (FK) is a threatening eye disease that if not treated quickly, can result in blindness.Ayurvedic and Indian traditional medicines for their medicinal properties, particularly in treating eye ailments. The current study aims to investigate the antifungal and antibiofilm effects of traditional Asian pigeon wing Clitoria ternatea flower extracts on the FK clinical isolate Coniochaeta hoffmannii and assess their potential as a topical agent for FK. The study used FTIR and GC-MS analysis to examine the structural details, key functional groups, and compounds in the extract with high antifungal activity. It also assessed the extract compounds' molecular docking structural affinity with fungal virulence and human inflammation-associated protein targets, toxicity screening, pharmacokinetic predictions, as well as CAE-EI anti-irritant and MTT cytotoxic tests. The CFEA (C. ternatea flower ethyl acetate) extract was found to possess strong antifungal and biofilm inhibitory properties. Several of its phytocompounds were also found to have no mutagenic potential, carcinogenicity, or eye irritation ability, and essential pharmacokinetic properties as a topical agent. Out of the 23 GC-MS identified compounds, 9,9-dimethoxybicyclo[3.3.1]nonane-2,4-dione-, Glycerol 1,2-diacetate, D-Glucitol, 1,4anhydro-, 1,2,3-Propanetriol, 1-acetate, and 2,5-O-Methylene-D-mannitol showed high in silico corneal permeability and strong interactions with fungal virulence cellobiose dehydrogenase, endo β 1,4 xylanase, and glucanase, as well as corneal inflammation-associated human TNF-α and Interleukin IL-1b protein targets. Additionally, the extract demonstrated the ability to reduce irritation and lack of toxicity. The findings indicate that extracts from C. ternatea flowers could be an effective and safe alternative for developing new topicalFK therapeutics.